2020
DOI: 10.1055/s-0040-1714698
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Manifestations of 3-Hydroxy-3-Methylglutaryl-Coenzyme-A Lyase Deficiency in Saudi Patients: Experience of a Tertiary Care Center

Abstract: Abstract3-Hydroxy-3-methylglutaryl-coenzyme-A lyase (HMGCL) deficiency, a rare autosomal recessive disorder, is caused by a homozygous or compound heterozygous mutation in the HMGCL gene (chromosome 1p36.11). HMGCL catalyzes the final step of leucine degradation and plays a key role in ketone body formation. Several studies have reported general hepatic findings (e.g., hepatomegaly) in patients with HMGCL deficiency, but currently, there are no available data regarding the incidence and epidemiology of liver i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Urine organic acids were indicative of HMGCL deficiency; glucose delivery was immediately doubled and 900 mg/kg/day S-DL-3OHB administered, leading to rapid resolution of clinical and biochemical findings. Whilst liver dysfunction is reported, liver failure is atypical for this disorder, and this type of presentation is more in keeping with a fatty acid oxidation disorder [ 6 , 28 ]. This case was the only one in our cohort that had quantifiable, though reduced, ketones in the urine and blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine organic acids were indicative of HMGCL deficiency; glucose delivery was immediately doubled and 900 mg/kg/day S-DL-3OHB administered, leading to rapid resolution of clinical and biochemical findings. Whilst liver dysfunction is reported, liver failure is atypical for this disorder, and this type of presentation is more in keeping with a fatty acid oxidation disorder [ 6 , 28 ]. This case was the only one in our cohort that had quantifiable, though reduced, ketones in the urine and blood.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified 211 cases, with an overall mortality of 16% [ 5 ]. A recent report from Saudi Arabia showed that all patients in their cohort of 62 patients had neurological complications [ 6 ]. Approximately 40% of reported patients presented in the newborn period with a rapidly progressive encephalopathy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%